Leading with soul an uncommon journey of spirit - Bolman, Lee G. (Jossey-Bass, 2001)
Since its original publication in 1995, this book has inspired thousands of readers. Far ahead of its time, it bravely reveals the path to leadership to be a personal journey requiring a knowledge of self and a servant-leader mentality. In this new and revised edition, the authors address such current issues as the changing nature of work, the new face of today's workforce, and the greater need for an infusion of soul in the workplace.